Complementation studies of the Arabidopsis fc1 mutant substantiate essential functions of ferrochelatase 1 during embryogenesis and salt stress. (19th November 2018) - Fan, Tingting; Roling, Lena; Meiers, Anna; Brings, Lea; Ortega‐Rodés, Patricia; Hedtke, Boris; Grimm, Bernhard
Abstract: Ferrochelatase (FC) is the final enzyme for haem formation in the tetrapyrrole biosynthesis pathway and encoded by two genes in higher plants. FC2 exists predominantly in green tissue, whereas FC1 is constitutively expressed. We intended to substantiate the specific roles of FC1. The embryo‐lethal fc1–2 mutant was used to express the two genomic FC‐encoding sequences under the FC1 and FC2 promoter and explore the complementation of the FC1 deficiency. Apart from the successful complementation with FC1, expression of FC2 under control of the FC1 promoter ( pFC1::FC2 ) compensates for missing FC1 but not by FC2 promoter expression. The complementing lines pFC1FC2( fc1/fc1 ) succeeded under standard growth condition but failed under salt stress. The pFC1FC2( fc1/fc1 ) line exhibited symptoms of leaf senescence, including accelerated loss of haem and chlorophyll and elevated gene expression for chlorophyll catabolism. In contrast, ectopic FC1 expression (p35S::FC1 ) resulted in increased chlorophyll accumulation. The limited ability of FC2 to complement fc1 is explained by a faster turnover of FC2 mRNA during stress. It is suggested that FC1‐produced haem is essential for embryogenesis and stress response. The pFC1::FC2 expression readily complements the fc1–2 embryo lethality, whereas higher FC1 transcript content contributes essentially to stress tolerance. Abstract : With the intention to substantiate the specific roles of Arabidopsis FC1, we analysed FC1 overexpressor lines and complementation lines of an fc1 knockout mutant expressing FC2 under the FC1 promoter. It is shown that the activity of the two FC variants are sufficient for embryo morphogenesis, but during salt and osmotic stress, FC1 expression is more appropriate than FC2 expression.